STUDY OF THE MULTICOLINEARITY OF THE EFFICIENCY CRITERIA OF THE OIL AND GAS WELL DRILLING PROCESS USING PDC-TYPE BITS - Скрип’юк, Ростислав; Кіліштоф, Іван (SWorldJournal, 2024)
Influence of function wear of armament of chisels is examined as PDC on driving of chisel, mechanical speed of driving, trip speed and prime price of meter of driving of oil and gas mining holes. It is rotined on the base of analysis of necessary terms o